Does The Consumers Materialism Affect Their Green Behavior? - Dwinita Laksmidewi (Journal of The Community Development in Asia, 2022)
The millennial generation is creative, innovative, and cares about sustainability. However, compared to the previous generations, they are the most consumptive. This study investigates their materialism effect on their adaptation to green values, their involvement in environmental sustainability, and the behavior of buying green products. The research was conducted using a survey method on 312 millennial respondents in Jakarta, Indonesia. The research model was processed using PLS-SEM. The results show that the respondents have moderate-level materialism. Consumer materialism has a significant effect on the green value adopted, which significantly affects green behavior. Materialism and green values also significantly affect their involvement in environmental issues. Materialism has no significant direct effect on green behavior and does not directly affect the involvement of environmental issues. However, the effect of materialism on green behavior is mediated by green values. The main finding of this research is that moderate-level materialism of millennial consumers increases the value of environmental care and encourages their desire to buy environmentally friendly products. This finding suggests that using green products might help consumers express themselves as knowledgeable people and signify their success.